Strategi Pembelajaran Ekspositori dengan Mushaf Isyarat pada Program BTQ bagi Siswa Tunarungu - Maya Dwi Iriantika; Muhammad Wahyudi Hanggara; Stevia Reynata; Abu Bakar; Agung Prasetiyo; Muh Syamsul Arifin; Bahrul Ulum (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2026)
This study examines the application of expository learning strategies using Mushaf Isyarat in the Al-Qur'an Reading and Writing (BTQ) program for deaf students at SLB Eka Mandiri Batu. The background of this study is the limited access to Al-Qur'an learning for students with hearing impairments, despite legal provisions that guarantee their right to education. This study aims to describe the stages of teachers' application of expository strategies and to identify supporting and inhibiting factors in the learning process using Mushaf Isyarat. The approach used is descriptive qualitative, with data collection techniques including interviews, observations, and documentation. The results show that expository strategies are implemented across the stages of preparation, presentation, correlation, conclusion, and application, with an emphasis on visual and kinesthetic media to make the material easier to understand. The use of Mushaf Isyarat has been shown to help deaf students recognize Hijaiyah letters, understand makhraj, and increase their motivation to learn. The main supporting factors included the teachers' competence in sign language, parental support, and the availability of visual learning media. Meanwhile, the obstacles lay in varying levels of deafness and difficulty pronouncing letters.